Pesticide contamination and associated ecological risks in estuarine waters of Brazil’s Legal Amazon - Viana, José Lucas Martins [UNESP]; dos Santos, Sara Raiane Viana; Santos, Lúcia H. M. L. M.; Jaén-Gil, Adrián; Rodríguez-Mozaz, Sara; Barceló, Damià; Franco, Teresa Cristina Rodrigues dos Santos (Springer Nature, 2025)
Pesticide contamination remains a significant environmental concern globally, with important implications for aquatic ecosystems. Despite being one of the world’s largest pesticide consumers, monitoring and assessment of pesticide pollution are limited in Brazil, especially in sensitive regions like the Amazon. In this study, the occurrence and environmental risks of 8 pesticides of different classes, namely alachlor, atrazine, chlorfenvinphos, isoproturon, irgarol, simazine, diuron, and its transformation product DCPMU (1-(3,4-dichlorophenyl)-3-methyl urea) were analysed in surface water of the São Marcos Estuarine Complex (SMEC) in two consecutive years. The quantification of the target compounds was performed using ultra-high-performance liquid chromatography–mass spectrometry (UHPLC-MS). Suspected and untargeted screening analyses with ultra-high-performance liquid chromatography–high resolution mass spectrometry (UHPLC-HRMS) was also conducted to identify transformation products (TPs) and additional pesticides in water samples. All target pesticides, except for alachlor, were found in at least one sampling campaign. The antifouling biocides irgarol and diuron were ubiquitous in 2018 and 2019, with detection frequencies varying between 81 and 100% and maximum concentrations of 13.6 ng L−1 and 17.1 ng L−1, respectively. In 2019, the detection frequencies of the target pesticides were considerably higher than in 2018, with atrazine, isoproturon, and DCPMU being found in 100% of the samples. In 2019, chlorfenvinphos and isoproturon were the pesticides with the highest levels, reaching 48.6 ng L−1 and 44.6 ng L−1, respectively. The UHPLC-HRMS analysis showed the presence of the pesticides DEET (N,N-diethyl-meta-toluamide), octhilinone (2-Octyl-4-isothiazolin-3-one), and cyprodinil (4-cyclopropyl-6-methyl-N-phenylpyrimidin-2-amine) in water samples. Additionally, the TPs 2-hydroxy-atrazine, didemethylisoproturon (1-(4-isopropylphenyl)urea) and M1 (2-methylthio-4-tert-butylamino-6-amino-s-triazine) were found. The environmental risk assessment showed that irgarol was the primary contributor to the global risk quotient in the SMEC region. Similarly, chlorfenvinphos also showed a high risk to the local aquatic biota, especially in 2019. This research not only highlights the urgent need for improved pesticide monitoring in Brazil but also establishes a baseline for future studies and environmental management efforts in SMEC. We emphasize the importance of prioritising pollutants and implementing effective mitigation strategies to protect the fragile aquatic ecosystems of the Brazilian Amazon.
Keywords: Antifouling; Estuary; HRMS; Pesticide; Risk assessment; Suspect screening